THE INFLUENCE OF LEARNING STRATEGIES AND LOGICAL THINKING SKILLS ON THE LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION AND ETHICS - Syamsu Nahar, Nurasyiah, Candra Wijaya, (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: the purpose of this study was to determine: (1) student learning outcomes taught by inquiry learning strategies and student learning outcomes taught using advanced organizer learning, (2) PAI learning outcomes and character about faraid students who have high logical thinking skills and students. who have low logical thinking skills, and (3) the interaction between learning strategies and students' logical thinking skills on the learning outcomes of Islamic Education and Characteristics about faraid. The study population was all students of class XI SMKN 1 North Region consisting of 2 classes. The sample chosen to be the inquiry learning class is class XI-1 and class XI-2 as the advanced organizer learning class. The sampling technique in this study was a cluster random sampling technique. The analysis varians technique was two-way at a significance level of x = 0.05 followed by the Scheffe test. The results of the study were: (1) the average learning outcomes of Islamic education and character about faraid students who were taught with inquiry learning strategies (= 28.35) were higher than the average learning outcomes of Islamic education and character about faraid students who were taught with strategies learning advanced organizer (= 26.97) with Fcount = 29.56> Ftable = 3.968, (2) the average Islamic education learning outcomes and character about students with high logical thinking abilities (= 30) were higher than the PAI learning outcomes and Characteristics about students with low logical thinking skills (= 26.06), with Fcount = 4.47> Ftable = 3,968, and (3) there is an interaction between learning strategies and logical thinking skills with Fcount = 9.88> Ftable = 3,968. The results of data analysis concluded that students with the characteristics of high logical thinking skills, the appropriate learning strategy to use was inquiry learning strategies and students with low logical thinking characteristics, the appropriate learning strategy to use was the advanced organizer learning strategy. The implications of this study are specifically targeted at the teaching staff.